Density functional study of spectroscopy, electronic structure, linear and nonlinear optical properties of l-proline lithium chloride and l-proline lithium bromide monohydrate: For laser applications - Haider Abbas; Mohd. Shkir; S. AlFaify (Arabian Journal of Chemistry, 2019)
Using density functional theory (DFT), a systematic study of structure, bonding, vibration, excitation energies and non-linear optical properties has been carried out for noncentrosymmetric l-proline lithium chloride monohydrate and l-proline lithium bromide monohydrate for the first time. The calculated vibrational frequencies and the S0 → S1 transition energy were compared with the earlier reported experimental results and found in good agreement. HOMO–LUMO energy gap was calculated by CIS, B3LYP and CISD using 6-31G(d,p), 3-21G, 6-31++G respectively and the obtained results are compared. For the calculation of excitation energies we used time dependent DFT (TDDFT). Both the molecules show the considerably lower dipole moment in excited state in comparison with the ground state. Mulliken charge and molecular electrostatic potential were studied. The first order hyperpolarizability for LPLCM and LPLBM are 2.15675 × 10−30 esu and 3.78984 × 10−30 esu respectively which are 5 and 10 times higher than prototype urea (0.3728 × 10−30 esu) molecule. The global chemical reactivity descriptors were also calculated. The calculated results of polarizability, first and second hyperpolarizability confirm that these molecules are good non-linear optical materials and can be used for laser device fabrications. Keywords: l-proline lithium chloride monohydrate, l-proline lithium bromide monohydrate, Vibrational analysis, Optical properties, Nonlinear optical materials, DFT